Gender and Sexuality in Stoic Philosophy - Grahn-Wilder, Malin (Springer International Publishing, 2018)
This book investigates the Ancient Stoic thinkers' views on gender and sexuality. A detailed scrutiny of metaphysics, ethics and political philosophy reveals that the Stoic philosophers held an exceptionally equal view of men and women's rational capacities. In its own time, Stoicism was frequently called ' the manly school' of philosophy, but this volume shows that the Stoics would have also transformed many traditional notions of masculinity. Malin Grahn-Wilder compares the earlier philosophies of Plato and Aristotle to show that the Stoic position often stands out within Ancient philosophy as an exceptionally bold defense of women's possibilities to achieve the highest form of wisdom and happiness. The work argues that the Stoic metaphysical notion of human being is based on strikingly egalitarian premises, and opens new perspectives to Stoic philosophy on the whole.